LEGAL QUALIFICATION OF ARTIFICIAL INTELLIGENCE: RESPONSIBILITY ISSUE - Murodiljon O. Orifjonov; Akhrorkhon A. Nabiraev (Scholars Digest Publishing, 2023)
In today’s world, many scholars argue whether Artificial Intelligence is a subject of law and must be responsible for the consequences of its actions; or whether it is a property, and the developers of AI technologies must be responsible for the mistakes of their creation. This article is aimed define the legal status and capacity of Artificial Intelligence by analyzing opinions of experts and existing legal practice. In the end we will specify the status of Artificial Intelligence and decide whether it is a subject or object of legal relations.
Keywords: artificial intelligence (AI), legal status, subject of law, object of law, legal capacity, legal regime, source of increased danger, intellectual property, electronic entity, robotic agents.